Relation of gossypol-gland density with bollworm incidence and yield in tree cotton (Gossypium arboreum) - MOHAN, PUNIT; SINGH, PHUNDAN; NARAYANAN, S S; RATAN, RAM (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season of 1989 and the summer and rainy seasons of 1990 to study gossypol-gland density in relation to bollworm Incidence and yield in 25 genetically diverse genotypes of tree cotton (Gossypium arboreum L.). A wide range of variability was oberved for gossypol glands per unit area on leaf, bract, calyx and ovary surfaces. The shape of gossypol glands wils spherical on leaf, bract and ovary surfaces; elliptical on stem and stigma surfaces; and both spherical and oval on calyx surface, Genotypes 'NAS 3','LD 230' and' Lohit' had high density of gossypol gland on their various parts. The elliptical gland was the largest and spherical gland the smallest. The genotypes with high gossypol-gland density on ovary surface showed low incidence of bollworms, viz american bollworm[Helicoverpa armigera (Hubner)], spotted bollworm [Earias vittella (Fabricius)] and pink bollworm [Pectinophora gassypiella (Saunders)] on the basis of loeules and higher seed-cotton yield/plant.